Altered regulation of cell migration in IRF6-mutated orofacial cleft patients-derived primary cells reveals a novel role of RhoGTPases in cleft/lip palate development - Al Saneh, Mounir (2021)
Cleft lip and/or palate (CL/P) affects on average 1 in 700 live births and is considered to be the most common congenital craniofacial birth defect (Setó-Salvia and Stanier 2014). It results from a failure in the lip buds and/or palatal shelves to properly position, proliferate, migrate, or fuse (Bush and Jiang 2012). In order to unravel the causes leading to the occurrence of the cleft, both genetics and molecular factors are being studied. The genetic approach consisted of collecting DNA samples from different families with CL/P and conducting targeted sequencing on all of them. Analysis of the generated reads consisted of aligning, annotating and calling the variants. This was followed by prioritization of candidate variants through several filtering steps. In the molecular part, we isolated two cellular populations from two patients: a control and a patient with a CL/P phenotype typical of van der Woude syndrome (VWS). We obtained primary cell cultures, specifically fibroblasts, derived from the anterior ossified region of the palate. The aim is to look for significant differences in the behaviour of the CL/P patient-derived cells in vitro when compared to control cells from the healthy donor through the study of different mechanisms, including cell proliferation, cell migration and adhesion. IRF6 targeted sequencing revealed mutations in two distinct families; one of the two mutations (p.Ala2Valfs*53), has not been reported in the literature previously. In the second family, a well-known mutation, p.Arg250Gln, was detected in an a priori isolated sporadic cleft. Our results showed that there is no difference in viability of the VWS patient cells compared to healthy control cells. However, a significant decrease in the migratory and adhesion ability of the VWS patient cells was detected compared to the control, which could account for the phenotype. The primary fibroblast cells of the affected individual with VWS showed a loss of directionality as was detected by the motility assays. Additionally, Rac1 activity was upregulated in the patient cells, and reflected by the accumulation of WAVE2 and Arp2 at the cell periphery resulting in a loss of productive migration, as opposed to their localization to a defined leading edge in motile healthy cells. The IRF6 mutation holds diagnostic value and provides better risk estimations. The results showed an increased understanding of the molecular mechanisms of VWS and expand the knowledge of its occurrence. They provide a strong molecular evidence that CLP/VWS phenotype could be caused by a defect in the migratory ability of the cell.